Prospective Study for the Use of Liquefied Natural Gas (LNG) as Fuel in Waterway Transportation - Gomes, Vera Lucia Lima; Mafra, Rosana Zau (Cadernos de Prospecção, 2025)
Natural gas has been used in various sectors of economic activity, from residential use, in thermoelectric plants, to as a fuel for automobiles. Considering that the state of Amazonas has the river transport as the main means of transportation for cargo and passengers and, at the same time, is a major national producer of this resource, the aim was to prospect the state of the art in technologies the uses liquefied natural gas as fuel for vessels in order to propose sustainable and economic improvements for the state. This is a quali-quanty study which data were collected from the Scopus and Orbit Intelligence databases, respectively; using the keywords “liquefied natural gas”, “storage tank”, “vessel”, “propulsion system”. The technologies identified, such as dual-fuel tanks or tanks that prevent LNG splashes, could be adopted on vessels in the state of Amazonas, contributing to the energy transition and sustainability.